The Common Assessment Used for English Teaching in Junior High School: a Naturalistic Study - Utomo, Aries (Proceeding of International Conference on Teacher Training and Education, 2016)
Assessment is used by a teacher in order to measure studentsâ ability in learning process. There are many kinds of assessment which can be employed to assess students in the classroom. The objective of this research is to describe assessment used for English teaching in high school. The design of this research was a naturalistic study. Object of this research was one state junior high school located in Surakarta. Based on the research data, assessment used by the English teachers consist of (1) formative assessment, (2) middle test, and (3) summative assessment. It can be concluded that the English teachers combine those assessment model in order to measure studentsâ ability in learning English at the school based on the 2006 curriculum where assessment are equipped by meaningful activities. In addition, those assessments seem complete if it is created constructively where assessments used are more focused on the studentsâ success than failure in learning.